Revisiting the transatlantic triangle : the constitutional decolonization of the Eastern Caribbean - Cox Alomar, Rafael (Ian Randle Publishers KingstonJM, 2009)
Focuses on Britain's colonial disengagement from the Eastern Caribbean. Evaluates the negotiating processes leading to the independence of Barbados in November 1966 and to free association with Britain for Antigua-Barbuda, St. Kitts-Nevis-Anguilla, Dominica, St. Lucia, St. Vincent and Grenada between February 1967 and October 1969.